Do Innovation Subsidies Crowd Out Private Investment? Evidence from the German Service Sector - Dirk Czarnitzki; Andreas Fier (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
This paper analyses the impact of public innovation subsidies on private innovation expenditure. In the empirical economic literature there is still no common support for the hypothesis of either a complementary or a substitutive relationship between public funding and private investment. We investigate whether firms of the German service sector increase their innovation effort when participating in public policy schemes. Cross-sectional data at the firm level are used to estimate the effect of subsidization. Applying a non-parametric matching approach we find evidence that the hypothesis of complete crowding-out effects between public and private funds can be rejected.
Keywords: C24; O31; H32; C20; 330; Innovation; Public Innovation Subsidies; Service Sector; Policy Evaluation; Innovationspolitik; Subvention; Forschungssubvention; Wirtschaftspolitische Wirkungsanalyse; Dienstleistungssektor; Innovation; Forschungsfinanzierung; Schätzung; Deutschland